Malaria knowledge and self-medication practices among local community of Papua - Zainuri, Agus; Arwimbar, Petrus YI; Irap, Samuel Piter (BKM Public Health and Community Medicine, 2024)
Purpose: Papua Province is Indonesia's largest contributor to malaria cases, accounting for 81% of the national malaria burden. These cases are concentrated in City of Jayapura, Jayapura Regency, Keerom, Mimika, Sarmi, Mamberamo Raya, Asmat, Boven Digoel, and the Yapen Islands. Given this high concentration, there is an urgent need for accelerated efforts to reduce malaria cases, particularly in these areas, to improve the overall malaria situation in Papua. Self-medication behavior plays a crucial role in malaria treatment, but fostering the desired knowledge and behavior around self-medication is challenging. This study surveyed the understanding of malaria and self-medication practices among the local population of Papua. Methods: The survey involved 100 respondents in areas with access to doctors and community health centers (Puskesmas) in Harapan Village, Jayapura Regency. Results: While there is strong knowledge about malaria transmission, significant gaps remain in safe self-medication practices, such as improper medication use and storage. These findings highlight the need for better public education on the importance of following medical instructions and seeking timely medical consultation when self-medication fails. Conclusion: Despite having relatively better access to a public health center, the local Papuan community still exhibits unsafe self-medication practices for malaria treatment. There is an urgent need to improve malaria treatment literacy and educate the community on proper treatment behaviors to ensure more effective malaria control.